ANALISA PENGARUH PENDIDIKAN DAN PELATIHAN SERTA PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PUSAT ADMINISTRASI UNIVERSITAS ISLAM SUMATERA UTARA - Zefrinizal Nasution; Deni Karli; Kamaruddin Kamaruddin; Budiati Budiati; Umi Nadrah (Manajemen dan Bisnis, 2022)
The formulation of the problem in this study is how the influence of education and training as well as career development simultaneously on the performance of the employees of the Administrative Center of the Islamic University of North Sumatra. This study aims to determine the effect of education, training as well as career development simultaneously on the performance of the administrative center employees of the Islamic University of North Sumatra. The sample in this study were all 61 employees of the Administrative Center of the Islamic University of North Sumatra. The data analysis technique in this study was Multiple Linear Regression. The results of this study indicate that education partially has a positive and significant effect on employee performance; Partial training has a positive and significant effect on employee performance; Career development partially positive and significant effect on employee performance; Education, training and career development simultaneously have a positive and significant effect on employee performance